The Influence of Organizational Culture and Motivation on Performance Through Job Satisfaction as an Intervening Variable at PT. Idea Creation Warehouse - Munawwarah, Muthii’atul; Chaerudin, Chaerudin (Indonesian Journal of Business Analytics, 2024)
Companies are aware that having a good relationship by providing services is important. Like PT. Gudang Kreasi Idea, company operates in the field of publishing and training services as well as educational consulting and continues to be committed to its vision and mission. This research aims to determine the influence of organizational culture and motivation on performance through job satisfaction as an intervening variable. 123 employees participated in this study. quantitative study utilizing SmartPLS 3 software for SEM-PLS data processing. The study's findings indicate that organizational culture significantly and favorably affects worker performance. The performance of employees is positively and significantly impacted by motivation as well. Additionally, a positive and significant impact of company culture on job satisfaction was discovered. Similarly, job satisfaction benefits greatly and is positively impacted by motivation. Then, there is a good and noteworthy correlation between job happiness and worker performance. Additional results of this study show that motivation influences worker performance through job satisfaction as an intervening variable and organizational culture influences worker performance through job satisfaction.